Chromosome aberrations in peripheral lymphocytes of workers employed in the plywood industry. - Kurttio, Päivi; Norppa, Hannu; Jarventaus, H.; Sorsa, Marja; Kalliokoski, Pentti (Scandinavian Journal of Work, Environment & Health, 1993)
Workers employed in sawmills and in the manufacture of plywood are exposed to potentially mutagenic chemical aromatic emissions from wood. However, very little is known about the exposure to these natural wood components. In an attempt to determine whether such exposure could have clastogenic effects, a group of 13 male nonsmoking employees mainly from the beginning of the wood-processing line of three plywood mills and 15 matched nonsmoking referents were studied for chromosome aberrations in blood lymphocytes. A statistically significant elevation of the frequency of cells with chromatid-type breaks (mean 2.1%), as compared with the corresponding frequency of the referents (mean 1.0%), was observed for the lymphocytes of the wood workers. These results lend support to previous studies which suggested that wood-drying fumes may be carcinogenic.